Andrew Hall Macpherson (1932-2002) - Miller, Frank L. (ARCTIC, 2002)
. As a teenager, Andrew was already living adventures that are the dreams of many teenage boys. From 1949 to 1957, before joining the Canadian Wildlife Service (CWS), he gained a lifetime of memories and valuable experience as a member of eight scientific expeditions to the Canadian Arctic. He served as a seasonal field assistant to scientists, working on contracts for the Department of Mines and Technical Surveys, the Defence Research Board, the Arctic Institute of North America, the Department of Northern Affairs, and the National Museum of Canada. He made most of his early trips to the Arctic in the company of his mentor and lifelong friend Thomas (Tom) Henry Manning, famed Arctic explorer and geographer-biologist. . His time in the Arctic convinced Andrew that he wanted to be an Arctic wildlife biologist. So, after completing a B.Sc. degree in Zoology (geology and geography) in 1954 at Carleton College, Ottawa, he went on to complete a M.Sc. in Zoology in 1957 at McGill University, Montreal. . In April 1958, he joined the CWS to work on Arctic wildlife problems. With glowing annual appraisals, he moved up through all the grades of biologist (I-IV) in only six years . He continued his studies at McGill and in 1967 received a Ph.D. for his seminal study, The Dynamics of Canadian Arctic Fox Populations. . In August 1967, Andrew left the Canadian Wildlife Service for a temporary position on the staff of the Science Secretariat, Science Council of Canada, as a project officer for studies in Canadian biological science. Once again, he expressed his desire to be a moving force, or at least a significant contributor to meaningful advances. . In 1970, a promotion to Director, Western & Northern Region, of the Canadian Wildlife Service brought Andrew to Edmonton, Alberta. .He . remained regional director of CWS until 1974. When the department reorganized into five regions, Andrew took a significant promotion to Regional Director General, Environment Management Service, Environment Canada, Western & Northern ...